“Not an Engineer Yet”: Manifestations of Liminal Engineering Identities - Stephanie A. Claussen; Janet Y. Tsai; Kathryn Johnson; Jenifer Blacklock; Jon A. Leydens (Studies in Engineering Education, 2023)
Background: Prior work has shown the importance of engineering identity formation for student success and persistence in engineering. While research has explored how engineering identity is formed, less attention has been given to liminal engineering identities—identities that exist between two commonly identified ones, such as the identity of being an engineering student and that of being an engineering professional—and the qualities of liminality that might impact this identity formation. Purpose/Hypothesis: This paper addresses the research question, “How do engineering students talk about their liminal engineering identities?” Design/Method: Through eleven focus groups held with engineering students at two U.S. universities, evidence of liminal engineering identities emerged. Focus group data was analyzed iteratively using an inductive analysis process due to the emergent nature of this study. Results: Our analysis found six categories for the reasons and justifications students gave for their liminal engineering identities: Mindsets and Related Personal Characteristics; Knowledge; Experience; Engineering Coursework and Degrees; the “Real World”; and Other People. We found that these categories sat on a continuum between an internal or self-driven sense of identity and an external or other-driven sense of identity. Conclusions: This work applies the concept of liminal identity to engineering education, emphasizing that engineering identity is more than an either/or prospect. It makes evident the intricate and intersecting ways in which students construct and justify their emerging engineering identities, and illuminates the reasons students give for refraining from fully adopting an engineering identity.